School Strategic Programs And Student Efforts Fostering Achievement Motivation In Madrasah Aliyah Negeri - Irwan Saleh Dalimunthe (IAIN Padangsidimpuan, 2020)
The study was conducted to find out the strategic effort in increasing achievement motivation as a trigger factor of student effort. This study administered some instrument in collecting the data such as interviews, observation, focus group discussion. Other data was gained from documents. It was found that the systems which were implemented in this school are first, involving many teachers to carry out the extracurricular activities and second, creating a full day school, because in the afternoon until late at night the students were mostly in school. Many students come from various regions to pursue diverse opportunities to improve learning achievement. Life challenges as a boarding boy which is relatively free at their boarding house encourage them to have high achievement motivation. Some of them even stronger in which they work part time to fulfill their school fee and be able to ward off all the challenges and glamorous lifestyle around their dwelling which has lots of social facilities such as online game houses, cafes and 24-hour food outlets; promiscuity and other morality abuses. Athough there are still little number of the students who were dropped out from school as a result of being unable to control themselves but there exist a number of successful students and their achievements increase rapidly that take them to higher education